THE EFFECT OF THE DIFFERENT DOSES OFAspergillus oryzae STARTER ADDITION ON THE QUALITY OF SKIPJACK (Katsuwonus pelamis)KATSUOBUSHI - Zurrahmi, Hafi; Sukirno, Sukirno; Leksono, Tjipto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbtrackThe study was aimed to observe the effect of addition Aspergillus oryzae starter at different doses on the quality of skipjack(Katsuwonuspelamis) katsuobushi and to determine the optimum dose of the starter added to produce the best quality of katsuobushi. Starter doses that used were 0 mL (D0), 1 mL (D1), 3 mL (D3), 5 mL (D5) and 7 mL (D7). The katsuobushi produced were then evaluated for their organoleptic value, including the appearance, aroma, texture and the taste, their physical and chemical characteristics, including water content, ash and phenol content, as well as the microbiological characteristics,including their total number plate count of bacteria and the fungi identification. The results showed that addition of different doses of Aspergillus oryzae starter was significantly affected to the value of appearance, aroma, taste, moisture content, ash, phenol and total bacteria. Addition of 1 mL (D1) starter produced the best quality of katsuobushi, indicated by the highest value of appearance (8,55), aroma (8,61) and taste (8,68). The fungi grew on each treatment was identified as Aspergillus sp. Keywords: Aspergillus oryzae,katsuobushi,skipjack, starter